Revisiting Buddhism in Ilkhanid Iran : Archaeology, Toponymy and Visual Culture - Kadoi, Yuka (Acta Mongolica, 2022)
It is generally agreed that Buddhism, which already came to be known in West Asia during the Sasanian period through commercial exchanges with India, revived in Iran under the Ilkhanids. A pioneering study of Buddhist-Islamic interactions by Elverskog (Buddhism and Islam on the Silk Road, 2010) amply demonstrates the importance of the Mongol period for the understanding of the religious contacts between Buddhists and Muslims, with particular reference to the role of Tibet in this unique socio-cultural as well as scientific encounter (the latter subject is explored by several studies, notably Islam and Tibet – Interactions along the Musk Routes, 2016). On the other hand, it remains a challenging task as to how the impact of Buddhism on the visual and material culture of Ilkhanid Iran should be reassessed, apart from attributions of unusual architectural remains to former Buddhist sites or interpretations of Buddhis iconographical elements found in manuscript paintings and decorative objects.